Between green and turquoise management styles - Sulich, Adam; Rutkowska, Małgorzata (Między zielonym a turkusowym stylem zarządzania, 2019)
Metaphors and colours can support a description of the organization culture and management styles, and between these descriptions are visible relations. Therefore, there are two highly developed management styles, green and turquoise. In these concepts, some different values are applied to employees, not just to innovative equipment and technology. The main difference between green and teal (turquoise) management is that the source of the organisation performance is intertwined with the all characteristics of the organisation’s members. The article presents the stages of development of management styles included in the colour characteristic of certain types of organizations, from the most basic to intelligent. There are different models of organizations which can be also described in the evolutionary approach. The purpose of the article is to provide descriptions of management styles specific to green and turquoise organizations
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 4, s. 24-31
Keywords: teal organization; turquoise organization; green organization; management styles; organizacja turkusowa; organizacja zielona; style zarządzania